Under-Ice Phytoplankton Blooms: Shedding Light on the “Invisible” Part of Arctic Primary Production - Mathieu Ardyna; C. J. Mundy; Nicolas Mayot; Lisa C. Matthes; Laurent Oziel; Christopher Horvat; Eva Leu; Philipp Assmy; Victoria Hill; Patricia A. Matrai; Matthew Gale; Igor A. Melnikov; et al. (Frontiers in Marine Science, 2020)
The growth of phytoplankton at high latitudes was generally thought to begin in open waters of the marginal ice zone once the highly reflective sea ice retreats in spring, solar elevation increases, and surface waters become stratified by the addition of sea-ice melt water. In fact, virtually all recent large-scale estimates of primary production in the Arctic Ocean (AO) assume that phytoplankton production in the water column under sea ice is negligible. However, over the past two decades, an emerging literature showing significant under-ice phytoplankton production on a pan-Arctic scale has challenged our paradigms of Arctic phytoplankton ecology and phenology. This evidence, which builds on previous, but scarce reports, requires the Arctic scientific community to change its perception of traditional AO phenology and urgently revise it. In particular, it is essential to better comprehend, on small and large scales, the changing and variable icescapes, the under-ice light field and biogeochemical cycles during the transition from sea-ice covered to ice-free Arctic waters. Here, we provide a baseline of our current knowledge of under-ice blooms (UIBs), by defining their ecology and their environmental setting, but also their regional peculiarities (in terms of occurrence, magnitude, and assemblages), which is shaped by a complex AO. To this end, a multidisciplinary approach, i.e., combining expeditions and modern autonomous technologies, satellite, and modeling analyses, has been used to provide an overview of this pan-Arctic phenological feature, which will become increasingly important in future marine Arctic biogeochemical cycles.

Spatial Heterogeneity as a Key Variable Influencing Spring-Summer Progression in UVR and PAR Transmission Through Arctic Sea Ice - Lisa C. Matthes; C. J. Mundy; S. L.-Girard; M. Babin; G. Verin; J. K. Ehn (Frontiers in Marine Science, 2020)